2017
DOI: 10.1177/1747493017694386
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and utility of an integrated medical imaging and informatics smartphone system for management of acute stroke

Abstract: Background Rapid dissemination and coordination of clinical and imaging data among multidisciplinary team members are essential for optimal acute stroke care. Aim To characterize the feasibility and utility of the Synapse Emergency Room mobile (Synapse ERm) informatics system. Methods We implemented the Synapse ERm system for integration of clinical data, computerized tomography, magnetic resonance, and catheter angiographic imaging, and real-time stroke team communications, in consecutive acute neurovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
1
16
0
4
Order By: Relevance
“…The study results show that the smartphone application yielded an accurate diagnosis of anterior intracranial arterial occlusion in times similar to diagnoses completed using the hospital-based desktop PC monitor. Several studies have reported the use of smartphone applications for the management of stroke [ 4 , 13 - 15 ]; however, no study has reported their use for assessing LVO. To the best of our knowledge, this is the first article to examine interdevice agreement and compare interpretation times for MRA and HVS on FLAIR imaging between a smartphone application and a hospital desktop PC monitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study results show that the smartphone application yielded an accurate diagnosis of anterior intracranial arterial occlusion in times similar to diagnoses completed using the hospital-based desktop PC monitor. Several studies have reported the use of smartphone applications for the management of stroke [ 4 , 13 - 15 ]; however, no study has reported their use for assessing LVO. To the best of our knowledge, this is the first article to examine interdevice agreement and compare interpretation times for MRA and HVS on FLAIR imaging between a smartphone application and a hospital desktop PC monitor.…”
Section: Discussionmentioning
confidence: 99%
“…The study results show that the smartphone application yielded an accurate diagnosis of anterior intracranial arterial occlusion in times similar to diagnoses completed using the hospital-based desktop PC monitor. Several studies have reported the use of smartphone applications for the management of stroke [4,[13][14][15]; however, no study has reported their use for assessing LVO.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Studies have recently been conducted to remotely check the clinical aspects, data, and scans of patients through smartphones to provide better treatment for patients with acute ischemic stroke. 15 16 17 Despite the limitations of small-scale research conducted in a single hospital, a recent study showed a reduction in door-to-needle times of 40 minutes using a mobile app in the prehospital setting. 18 Consistent with prior studies, these results were confirmed in our study in a metropolitan setting; when the FASTroke app was activated, the percentage of patients who received reperfusion treatment was 9.8% higher for IVT alone and 11.3% higher for IVT plus EVT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other reports of mobile apps being successfully deployed with similar results. 9,10 Increased visibility of team performance and immediate feedback from the app are additional motivators for improvement. Stroke care is unique in that a considerable amount of evaluation over separate facilities is required in a relatively narrow window, thereby making such a mobile app-based strategy especially valuable.…”
Section: Editorialmentioning
confidence: 99%
“…There have been other reports of mobile apps being successfully deployed with similar results. 9,10 Stroke care is unique in that a considerable amount of evaluation over separate facilities is required in a relatively narrow window, thereby making such a mobile app-based strategy especially valuable. Similar app-based solutions are already available for myocardial infarction, trauma and sepsis.…”
Section: Editorialmentioning
confidence: 99%